Speech Acts in the Lyrics of 'About You' by The 1975: A Semantic Study - Novemty Tampubolon; Bernike Anggita Ristia Damanik (Yayasan Literasi Sains Indonesia, 2026)
This study examines the types and illocutionary forces of speech acts in the song